STUDY OF OBTAINING AN ORGANOMINERAL MODIFIER FROM LOCAL RAW MATERIALS TO IMPROVE THE OPERATIONAL PROPERTIES OF BITUMEN - Ikromov, M (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article presents information on the physicochemical properties of the selected raw materials based on local materials and the technology for obtaining an organomineral modifier from it. To modify road bitumens and increase the resistance of road pavements obtained on their basis to rapidly changing weather conditions, technological, rheological, physical-mechanical, and deformation effects, as well as to increase their wear resistance, ingredients based on local raw materials were selected, their physicochemical properties were studied, and a technology for obtaining an organomineral modifier based on them was developed.